Cognitive-Discursive and Sociopragmatic Features of 1st and 2nd Person Pronouns: Across Different Languages and Cultures - Pazilova , Nasibakhon (The Lingua Spectrum, 2025)
This article analyzes the cognitive-discursive and sociopragmatic features of singular and plural 1st and 2nd person pronouns within the context of various languages and cultures. It explores the intricate connections between pronouns and grammar, communication, and culture, as well as their distinctions based on social distance, formality, gender, and number. The universality and national characteristics of personal pronouns in English, Russian, Uzbek, Arabic, Korean, Japanese, Persian, and European languages are compared. Using cognitive and sociopragmatic approaches, the study reveals how personal pronouns function in linguistic, psychological, and cultural contexts. The findings emphasize the crucial role of pronouns as mechanisms of subjective and intersubjective classification in human cognition, and their linguocultural function in expressing social relationships and communicative norms across different cultures.